ANALISIS KEANEKARAGAMAN JENIS VEGETASI MANGROVE DI KAWASAN HUTAN LINDUNG ANGKE-KAPUK DAN TAMAN WISATA ALAM ANGKE-KAPUK MUARA ANGKE KOTA JAKARTA UTARA - Khoe Susanto Kusumahadi; Ahmad Yusuf; Rizky Gautama Maulana (Universitas Nasional, 2020)
This research based on the tendency of the decline in the function and degradation of mangrove forest areas in the Jakarta Bay, namely AngkeKapuk Protection Forest (HLAK), and Angke-Kapuk Nature Tourism Park (TWA), which can cause this area to be no longer suitable for all life the wild there. Therefore this study aims to determine the diversity of mangrove vegetation types in the HLAK and TWA Angke-Kapuk areas of North Jakarta. By using a descriptive qualitative process research method, with the concept of Magurran (1987), it was concluded that Diversity (H ') in HL AngkeKapuok and TWA Angke-Kapuok in each stand was classified as low, namely tree H' = 1.03, tillers H '= 1.56 and seedling H '= 1.23. The composition of mangrove vegetation types recorded at HL Angke-Kapuk and TWA AngkeKapuk contained 11 tribes, 14 genera and 16 species. The highest Importance Value Index in HL Angke-Kapuk and TWA Angke-Kapuk each of the stands starting from seedlings and tree species are Aviennia marina with a seedling value of 205.15%, sapling rate175.01% and tree level 225.72%.